INFLUENCES OF NONLINEAR SUSPENSION ON THE BUS’S ROLL STABILITY BY A LATERAL DYNAMIC 4-DOF MODEL - Huu Nhan, Tran; Ngoc Dai, Pham (Journal of Applied Engineering Science, 2023)
The influences of nonlinear suspension system with air spring and nonlinear asymmetrical (NA) absorber in comparison with a linear suspension is analyzed based on a lateral dynamic four degrees of freedom (4-DOF) model. The lateral dynamic model considers the effects of anti-roll bars, the roll center position, and the transient excitation of the road on the roll stability performance. The characteristics of the suspension system, the position of the roll center, the road excitation load all play very important roles in determining the roll stability of the vehicle. The maximum dynamic roll angle with nonlinear suspension is always smaller than that with linear suspension. The maximum dynamic rollover stability index is strongly dependent on the velocity and about 27% on average lower than that of linear suspension in the whole velocity domain, subjected under road excitation. However, the maximum of absolute acceleration is always larger with the nonlinear suspension system.